Meta-cleavage pathway of phenol degradation by Acinetobacter sp. strain AQ5NOL 1 - Ahmad S.A.; Shamaan N.A.; Syed M.A.; Khalid A.; Ab Rahman N.A.; Khalil K.A.; Dahalan F.A.; Shukor M.Y. (Springer-Verlag Italia s.r.l., 2024)
Indexed by SCOPUS